HCV Reactivation in a Patient with Hepatocellular Carcinoma Due to Sorafenib: A Case Report - Cheng J; Pan J; Zhao D; Ma X; Sun Q; Li J (International Medical Case Reports Journal, 2024)
Jun Cheng,* Jinjin Pan,* Dongmei Zhao, Xuejiao Ma, Qiulin Sun, Jiabin Li Department of Infectious Disease, The First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiabin Li, Tel/Fax +86-551-62922281, Email lijiabin@163.comAbstract: The global prevalence of hepatitis C virus (HCV) infection is approximately 3%, with a post-infection chronicity rate of up to 50%– 85%. HCV reactivation can occur when anti-HCV positive individuals receive antineoplastic therapy. In this study, we report a case of an anti-HCV positive patient with negative HCV RNA after 12 weeks of direct antiviral therapy. Two months later, sorafenib was used to treat hepatocellular carcinoma, and HCV reactivation occurred after 8 months of the treatment. HCV RNA was negative after 12 weeks of antiviral treatment with Sofosbuvir-velpatasvir. We also discussed the mechanism of HCV reactivation caused by sorafenib and the antiviral treatment regimen after HCV reactivation with the relevant literature.Keywords: hepatocellular carcinoma, sorafenib, HCV-RNA, anti-HCV therapy, reactivation